MOOD REALIZATION OF THE LEARNING ACTIVITIES IN THE GRADE VII ENGLISH TEXTBOOK PUBLISHED BY THE MINISTRY OF EDUCATION AND CULTURE (Universitas Negeri Semarang, 2015)
This present study is aimed at explaining the mood realization of the learning activities in the grade VII English textbook published by the Ministry of Education and Culture. It is designed within the framework of qualitative research and the method is discourse analysis. The result shows that the learning activities give more imperative mood than the others. Afterwards, speaking skill is included more than the other skills.To achieve communicative activity, the good balance between indicative and imperative mood should be realized in the process of teaching and learning English. Although teacher has a powerful authority and that is natural since teacher is the leader in the classroom, the process of giving and demanding information between teacher and students could be realised to achieve communicative activity. Subsequently, despite the percentage of speaking is the highest, listening has the least percentage in this textbook. Listening is importance in our class since English is the students’ foreign language. Therefore, it is essential that listening activities should be included in a balanced portion with speaking activities in order to understand spoken discourse.